Content Analysis of Gorontalo Dikili Manuscript and the Relevance to Message and Values of Kindness - N. Hula, Ibnu Rawandhy; Helingo, Adimawati (Pusat riset dan Inovasi Nasional, 2022)
The study aims to analyze the content of the Gorontalo Dikili manuscript and its relevance to messages and values ​​of kindness. This research is library research with a descriptive qualitative approach. Primary data were collected and identified through documents in the form of manuscripts and written with APG script, totalling 10 main themes and containing 297 couplets. Secondary data in the form of video recordings The data is processed following the stages of philological analysis by reading the manuscript, identification, editing, and interpretation. The interpretation technique is done by directed content analysis. The results of this study indicate that the manuscript in Gorontalo contains messages and values of kindness that can be used as lessons and examples in following the sunnah of the Prophet. The values ​​of goodness include: The value of spiritual education is related to patience and independence as an orphan. Moral values, in the form of fair behaviour in acting and behaving. Cultural values ​​are related to the recommendation of circumcision which is useful for maintaining genital hygiene for men, maintaining the respectfulness of women to avoid disgraceful attitudes and traits, and tolerant behaviour toward adherents of other religions. Social value is found in the sincere attitude of giving and willing to share, and always giving benefits to others. This research has implications for information about the contents of the dikili manuscript which has not been revealed, so the celebration of the prophet's birthday by re-reading the prophet's life history text needs to be preserved.